Water–solids interactions, matrix structural properties and the rate of non-enzymatic browning - Acevedo, Nuria (2006)
The kinetics of non-enzymatic browning (NEB) was studied in freeze-dried model and food systems in a wide range of relative humidity (R.H.) values. PVP, lactose, lactose–starch solutions and food (milk, cabbage, apple, potato, and chicken meat) systems were freeze-dried, equilibrated at 11–85% of R.H. and incubated at 70 C. Thermal transitions were determined by DSC. The kinetics of NEB development was analyzed. In PVP systems the maximum rate occurred at 33% R.H., at which Tg was close to the storage temperature. Above 33% R.H. the samples presented a fluid aspect at 70 Cand the NEB rate decreased when increasing R.H. In tissues containing structuring water insoluble biopolymers and presenting an intermediate degree of collapse, the maximum rate of NEB occurred at relative humidities in a range of 50–80%, when the samples were well above Tg at the storage temperature. In the lactose systems the maximum rate occurred at R.H. close to 40%, at conditions at which lactose was highly crystalline.